Neue Ansätze der Politischen Geographie und Geopolitik - Boesler, Klaus-Achim (ERDKUNDE, 1997)
In recent times, space, location and spatially-tied resources experienced a dramatic loss in significance for political action. Regional identity, on the other hand, together with distinctive risks and features of time and space have increasingly gained importance as themes. These factors have led to changes in the approaches of political geography, and simultaneous consequences for a Neue Geopolitik. It is in this context that this paper examines the changed concepts of territoriality and regional identity, the different forms of political regionalism in Europe, the effects of globalisation and the present assymetry of geographical structures in Europe. This in turn lends itself to the derivation of approaches to a new geopolitics. In this geopolitics is principally understood as an interdisciplinary theory of evaluation patterns in relation to time and space, which are used by those who are politically involved, and of the resulting political structures of space. Their theoretical foundations constitute the findings of all the sciences which touch upon politics, such as political geography.